“Gray Murder”: Characteristics of Elderly Compared With Nonelderly Homicide Victims in New York City - Abrams, Robert C. (© American Journal of Public Health 2007, 2007)
Objectives. We compared characteristics of homicides among New York City residents aged 18 years and older from 1990 to 1998 to determine differences in demographics, cause and place of death, and presence of illicit drugs and alcohol in the deceased’s system. Methods. All medical examiner–certified homicides among New York City residents aged 18 years and older from 1990 to 1998 were studied (n = 11 850). Nonelderly (aged 18 to 64 years) and elderly (aged 65 years and older) victims were compared by gender, race/ethnicity, cause of death, place of death, and presence of illicit drugs or alcohol. Population-based homicide rates stratified by age, gender, and race were also calculated. Results. Nonelderly homicide victims were significantly more likely to be male, non-White, to have been shot in the city streets, and to have evidence of illicit drug or alcohol use. Elderly victims were more likely to be female, White, to have been killed by nonfirearm injuries, and to have been killed in their own homes. The gender and race differences between age groups remained but were attenuated when population-based rates were compared. Conclusions. The characteristics of homicide in nonelderly adults do not apply to elderly adults in New York City. Demographic factors and vulnerabilities of the elderly may underlie these differences, pointing to the need for oversight of isolated or homebound elderly persons and for protective interventions.